تحسين أداء شبكة نقل المعطيات الهجينة منخفضة السرعة والمستخدمة في المنشآت العاملة في الزمن شبه الحقيقي. (Latakia University Journal -Engineering Sciences Series, 2016)
أدى انتشار تطبيق تقنيات نقل المعطيات الحديثة، في مجالات صناعية، وزراعية، وخدمية متنوعة إلى ضرورة نقل هذه المعطيات، ضمن أجزاء المنشآت، بفعالية ومرونة. يهدف البحث إلى تطبيق آلية هجينة، تعتمد على استخدام تقنية ZigBee، وتقنية CAN Bus معاً، بما يعطي أداء أفضل، وفقاً لمعايير الأداء التي يتطلبها عمل شبكات هذه المنشآت، في الزمن شبه الحقيقي. ومقارنة هذه الآلية مع الآليات المقترحة في أبحاث مشابهة. يعتمد الحل المقترح استخدام شبكات نقل معطيات هجينة، تعتمد على وصل الشبكات الجزئية، التي تعتمد تقنية CAN Bus، باستخدام عمود فقري لاسلكي يعتمد تقنية ZigBee. واقتراح بنية مناسبة لبوابات العبور بين أجزاء الشبكة الهجينة. أثبتت النتائج أن الآلية المقترحة في هذا البحث أفضل مقارنة بأبحاث مشابهة، وفقاً لمعايير أداء مناسبة لمثل هذا النوع من الشبكات، بما يسمح لنا بالتوصية باستخدام هذه الآلية في التطبيقات الصناعية الخدمية. وقد اعتمد البحث على المحاكي الشبكي NS2 لتقييم النتائج ومقارنتها. The spread of the modern data transfer techniques, in modern industrial and agricultural applications, and service areas, leads to the need to transfer this data effectively and flexibly, within installations parts.This research aims to apply the hybrid mechanism, based on the use of ZigBee technology, and CAN Bus together to ensure the best performance, in accordance with the performance indicators required by the networks of these facilities, in near-real time operation. The study attempts to compare this mechanism with other mechanisms proposed in similar research.The proposed solution supports the use of a hybrid data transfer networks, based on the internetworking of CAN Bus networks, using a backbone based on wireless ZigBee technology. This solution proposes an appropriate structure for gateways between the hybrid parts of the network. The research has concluded that the proposed mechanism preference, compared with the proposed mechanisms in similar research, according to the standards of performance indicators, is suitable for this kind of networks, as it allows us to recommend the use of this mechanism in the service and industrial applications. The NS2 network simulator is used to evaluate and compare the obtained results.